Visible light-driven g-C3N4 peroxymonosulfate activation process for carbamazepine degradation: Activation mechanism and matrix effects. (January 2022) - Cheng, Zihang; Ling, Li; Fang, Jingyun; Shang, Chii
Abstract: In this study, g-C3 N4 with a high portion of tri-s-triazine groups was synthesized to activate peroxymonosulfate (PMS) under visible light irradiation, termed as Vis/g-C3 N4 /PMS process, to degrade one frequently detected recalcitrant micropollutant carbamazepine (CBZ). The Vis/g-C3 N4 /PMS process increased pseudo first-order degradation rate constant of CBZ by 2 times compared with that in the absence of PMS. The enhanced CBZ degradation was because of the production of HO and SO4 – from the PMS activation, but not the enhanced charge separation of g-C3 N4 due to the presence of PMS. The Vis/g-C3 N4 /PMS process is insensitive to dissolved oxygen, chloride and bicarbonate concentrations, effective over a wide pH range from 6.0 to 10.0, and less affected by high concentrations of natural organic matter compared with the UV/chlorine and UV/TiO2 processes. In addition, photocatalytic activity of g-C3 N4 remains stable over 5-cycle of reuse. These features make the process practically relevant and implementable in degrading micropollutants in drinking water, treated wastewater, surface water, groundwater, etc., using more efficient visible light LEDs or even sunlight. Graphical abstract: Image 1 Highlights: Photo-induced e c b − and O2 – activate PMS to produce SO4 – and HO. SO4 – and HO are responsible for the enhanced carbamazepine degradation. Shorter irradiation wavelength and higher intensity enhance the radical generation. Dissolved oxygen, chloride and bicarbonate have little impact on the process. Tri-s-triazine structures in g-C3 N4 mitigate the adverse impact of NOM on the process.